MATHEMATIC MODEL AND OPTIMAL STRATEGY OF HIT PHENOMENA FOR INDONESIA COSMETIC BRANDS - Eka Pratiwi, Sukma
As the digital world develops, the term viral marketing (viral marketing) or also known as Word of Mouth (WOM) is known. Word of Mouth Marketing is implemented by utilizing Influencers and Brand Ambassadors, where business people pay internet celebrities to promote the products of the business they manage through social media. This study discusses the comparison of the Bass model and the Hit Phenomena model to see the effect of Word of Mouth on sales of Indonesian Cosmetic Brands. In the Bass model, changes in the total consumer population are reviewed by considering the rate of direct communication and indirect communication. Meanwhile, the Hit Phenomena model examines consumer populations and Brand Ambassadors separately, modified from the SIR-SI model. To obtain a communication rate that represents actual data, the Bass model estimates parameters using Nonlinear Least Square while the Runge-Kutta method of order 4 is used for the Hit Phenomena model. Phenomena constructed using a simple SIR-SI compartment model. Optimal control is used to minimize the number of Brand Ambassadors that must be contracted by the company. The results of numerical simulations on the optimal control problem show that self-promotion by companies and the interaction rate of Influencers and potential populations can reduce the number of Brand Ambassadors that companies have to contract.